MEMBANGUN MASA DEPAN PENDIDIKAN ISLAM: Belajar dari Sejarah dan Merespon Perubahan Zaman di Era Digital - Mohammad Sahlan; Mochamad Iskarim (Fakultas Agama Islam Universitas Islam Madura, 2023)
Islamic education has a rich historical heritage in preparing generations of Muslims with strong religious values ​​and deep understanding. However, with the fast-changing times with global challenges, Islamic education needs to adapt so that it remains relevant to the needs of the times. This researcher will explore Islamic education in response to changing times by using innovation and technology. Researchers will identify the history of Islamic education, the challenges of Islamic education and educational innovation, the role of teachers and institutions in building the future of Islamic education. The research method used was descriptive qualitative with a literature study approach, while the data sources in this study were reference books that were closely related to the research which the researchers then combined with interview techniques with educational experts and teachers to strengthen the primary data that the researchers obtained. in the field. The results of the study show that an understanding of the history of Islamic education is the basis for building a strong and relevant future. This research can also provide practical recommendations to practitioners and policymakers in the field of Islamic education to improve the quality of education and meet the changing demands of the times. While the implication is that it can provide a complete picture to education practitioners, be it teachers, implementers and sympathizers of education to get a complete picture of the reality of education.